Effects of Spironolactone on Diastolic Function in Patients with Heart Failure with Preserved Ejection Fraction - Alam, Md Tasnim; Mahmood, Manzoor; Huda, SM Nurul; Anowar, AFM Azim; Saha, Swadesh Kumar; Kabir, SK Nafis; Rahman, HN Ashikur; Khaled, Md Fakhrul Islam; Parvin, Tanjima; Ahmed, Khueshed; Ahmed, Chaudhury Meshkat; Haque, Harusul (University Heart Journal, 2025)
Background: Management of heart failure with preserved ejection fraction (HFpEF) patients have become more challenging than systolic heart failure as there is no effective therapy for HFpEF. Mineralocorticoid receptor antagonists (MRA) like spironolactone inhibits the effect of aldosterone and may lead to improvement of left ventricular diastolic function. Objective: To evaluate the effects of spironolactone on diastolic function in patients with HFpEF. Methods: This Randomized control trial was conducted in the Cardiology Department of BSMMU from June, 2022 to May, 2023. A total of 54 patients of HFpEF who had NYHA class II-IV features of heart failure with echocardiographic evidence of diastolic dysfunction were randomly assigned into 2 groups. Then patients of spironolactone group were given spironolactone 25 mg/day in addition to standard risk factor control treatment and patients of control group were monitored with standard risk factor control treatment only. Baseline and after 6 months clinical and echocardiographic data were compared. Results: Total 52 patients completed the follow-up, among them 26 were in spironolactone group and 26 were in control group. Early mitral inflow velocity and mitral annular early diastolic velocity ratio (Average E/e’) declined significantly after 6 months of spironolactone treatment (P value = .011). Septal e’ and lateral e’ were improved significantly in spironolactone group (P value = .003 and < .001 consecutively). Analysis of diastolic dysfunction grade showed that diastolic dysfunction grades remained quite unchanged (P value= .370). Conclusion: Spironolactone played a significant role in improvement of some of the parameters of diastolic dysfunction (like average E/e’, septal and lateral e’) although any significant effect on change of diastolic dysfunction grade was not observed in this study. Keywords: Spironolactone, Diastolic dysfunction, Average E/e’, heart failure with preserved ejection fraction, HFpEF University Heart Journal 2025; 21(1): 9-16